Estudos de acoplamento molecular entre peróxidos obtidos de fontes naturais e o grupo heme - Leite, Franco Henrique Andrade (2011)
Artemisinin is a sesquiterpene lactone with an endoperoxide function currently used against strains Plasmodium falciparum. Endoperoxides are supposed to act on heme leading to reduction of the peroxide bond and production of radicals that can kill the parasite. In addition, recent studies have shown that artemisinin can inhibit the sarco/endoplasmic reticulum Ca2+-ATPase (SERCA) orthologue (PfATP6) of P. falciparum in Xenopus oocytes. Nowadays, malaria kills more than AIDS and the increasing parasite resistance to current drugs endorses the search for new therapies. In this study was proposed the identification of potential antimalarial drugs obtained from natural sources by molecular modeling. The main goal is to identify potential antimalarial drugs from natural sources, as well as identify possible correlations between in silico studies and experimental data. Thus, were studied the interaction of 51 peroxide with heme, comparing them with the values obtained for artemisinin. These peroxides were divided into two sets. The first set, called training set was composed of 10 artemisinin derivatives with known biological activity. The second set, called test set was composed of 40 peroxides present in nature with the primary focus of the compounds from Brazilian flora, which antimalarial activity has not been evaluated. Docking studies were performed in three steps. Firstly, a docking between artemisinin, 10 synthetic analogs and heme was carried out with AutoDock Vina 1.0.2. Then, the calculation of single-point in vacuum and solvent phase (PCM) followed by each complex optimization was performed with Gaussian 09W using the PM6 method. Finally, the correlations between the energies and the experimental data (inhibitory concentration (IC50) and dissociation constant (Kd)) were performed for all compounds of the training set. The correlation results indicated any significant (α = 0.01) between complex energy and Kd, -0,75 using Spearman test. The same computational protocol was performed realized for the test set. All natural peroxides selected showed molecular electrostatic potential (MEP) map similar to artemisinin, where the density of negative charge is located on the oxygens of the peroxide grouping. The results of final energy obtained at semi-empirical PM6, showed the compound "5" and "24" as promising antimalarial drugs. Thus, it is possible to identify that there are natural compounds with possible antimalarial activity, in which the modeling tool can guide the molecular identification of bioactive compounds and therefore the development of new drugs.